The Effects of Lower Extremity Rotational Malalignment on Pediatric Patient-reported Outcomes Measurement and Information System (PROMIS) Scores. Issue 8 (12th September 2022) - Chandrananth, Janan; Hannan, Richard; Bouton, Daniel; Raney, Ellen; Sienko, Susan; Do, Patrick; Bauer, Jeremy P.
Abstract : Background: There is sparse literature demonstrating the relationship between lower limb pediatric idiopathic rotational malalignment (IRM) and patient-reported outcomes measurement information system (PROMIS) scores. Our goal is to determine and quantify the amount that IRM deformities, as measured with the 3D gait analysis, affect childrens' pain interference, mobility, and peer relationship PROMIS domains. Secondary outcomes include investigating the potential relationships between IRM and various subgroups (Pediatric Outcomes Data Collection Instrument (PODCI), gender, Body Mass Index (BMI), femur Versus tibia). We also examine whether the PROMIS domains correlate with PODCI in this population. Methods: This study was a retrospective cohort, single institution, and consecutively recruited cases series. We identified 47 children over a 3-year period who were evaluated at the motion analysis center at our tertiary care hospital, with increased torsion of the femur or tibia. After exclusions, 25 children with IRM, documented PROMIS data and gait analysis were considered. Results: Femoral malrotation had a significant relationship with female gender ( P =0.001) and increased BMI ( P <0.001). Femoral malrotation had a correlation with PROMIS pain interference ( P =0.016), whereas tibial rotation did not achieve significance ( P =0.084). In the ANOVA regression analysis, there was a strong prediction of the PROMIS mobility domain when both malrotation and pain interference were present ( P =0.007). There were Pearson Correlations of PROMIS and PODCI domains for Mobility Versus Sports ( P =0.007) and Pain Interference Versus Comfort/Pain ( P =0.004), respectively. Conclusion: The evident relationship between lower limb rotational malalignment and PROMIS scores signifies the likelihood for gait and pain disturbance. This in turn could show us that children are likely to be more debilitated and thus may benefit from timely correction. We aim to conduct this as a multicentre trial to confirm our findings. Level of Evidence: Level IV.